Effets pervers de certaines luttes féministes sur le contrôle social - Snider, Laureen (Criminologie, 1992)
This paper analyses feminist initiatives to use law, particularly the criminal justice system, to heighten levels of control over men and fight partriarchy. It argues that passing new laws and increasing levels of punishment has not worked, either to strengthen individual female victims, or to build the feminist movement as a whole. Increasing punishment through criminal law means investing power in the hands of an un-monitored bureaucracy which has historically acted to promote a set of institutional, structurally based principles which are incompatible with feminist aims. The paper examines efforts to employ criminal and civil law in the struggle against patriarchy, in spheres such as rape and wife assault, and shows that inviting the state to intrude more deeply into the lives of lower and working class women has extended criminalisation and increased state control, without altering the underlying conditions which continue to create female victimization. The final section examines alternate measures to achieve feminist goals of empowerment and social transformation.